Pentingnya Dukungan Sosial Terhadap Perilaku Self-Harm Pada Remaja Yang Merasa Kesepian - Atiyah Faridah Hanan; Ati Kusmawati; Tanisa Eka Putri; Tiwi Oktaviani (Concept: Journal of Social Humanities and Education, 2024)
Adolescence is an important transition period in a person's life, where they experience significant physical, psychological and social changes. During this period, teenagers often face various pressures and challenges, including the problem that teenagers often face is loneliness. Prolonged loneliness can cause teenagers to feel isolated, hopeless, and have difficulty dealing with negative emotions. In this situation, teens may look for ways to ease the pain and achieve a temporary sense of relief. One response that may arise is self-harm behavior or self-injury. And to minimize the occurrence of self-harm, social support is very necessary. This research aims to gain a deeper understanding of how important social support is for self-harm behavior in teenagers who feel lonely. This research uses a qualitative approach and the method used is literature study. Meanwhile, the data collection technique in this research is a documentary study. The research results show that social support has an important role in self-harm behavior because social support can act as a protective factor in reducing the risk of self-harm behavior in lonely adolescents. The higher the level of social support received by adolescents, the lower the level of self-harm behavior they engage in.